Effects of Zuclopenthixol on Aggressive Disruptive Behavior in Adults with Mental Retardation – A 2-Year Follow-Up on a Withdrawal Study - Häßler, F.; Glaser, T.; Reis, O. (Pharmacopsychiatry, 2011)
People with mental retardation often display aggressive behavior against themselves or others making care within institutions or foster families difficult. Due to a lack of viable alternatives, antipsychotics of the first and second generations are often used for long-term treatment despite the fact that only data about short-term treatment exist.A short-time withdrawal trial of 12 weeks (n=39) was extended at open label to 2 years. 31 patients received zuclopenthixol after the end of the withdrawal and were examined using the same instruments as in the withdrawal period (DAS, MOAS, CGI).Patients still treated with zuclopenthixol after 2 years (n=21) benefitted, compared to the drop-outs (n=10). Analyses of time trends revealed an early effect of zuclopenthixol which could not be enhanced afterwards.Zuclopenthixol proved to be safe and effective to keep a lower rate of aggressive behavior in adults with mental retardation also over a longer period of time.
Keywords: mental retardation; aggression; zuclopenthixol; long-term results